Voltage-tunable dielectric properties of pyrochlore Bi-Zn-Nb-Ti-O solid-solution thin films - Kim, JY; Kim, DW; Jung, HS; Hong, KS (JAPAN SOC APPLIED PHYSICS, 2005)
The structural and dielectric properties of Bi2Ti2O7-Zn2Nb2O7 solid-solution thin films were investigated using (Bi2-xZnx)(NbxTi2-x)O-7 (BZNT, 0.05 <= x <= 1.0) pyrochlore thin films prepared on platinized Si substrates by metalorganic decomposition (MOD) process. Thermal analysis and X-ray diffraction (XRD) results confirmed that the crystallization of the BZNT thin films started below 600 degrees C and was completed at approximately 750 degrees C. Broad ranges of single-phase solid-solutions based on cubic (Bi1.5Zn0.5)(Nb0.5Ti1.5)O-7 were observed with x values from 0.1 to 0.7. Compared with bulk ceramics, a restriction in the lattice shrinkage of BZNT thin films with-x values under 0.5 was apparent, which may have introduced internal stress in the thin films and eventually affected the dielectric properties of BZNT thin films. The BZNT thin films investigated had dielectric constants in the range of 142-242, and the maximum dielectric constant was 242 when x = 0.5. Room-temperature capacitance-voltage measurements at 1 MHz demonstrated a tunability of 30%, with a zero-bias tan 3 of 0.005.
Keywords: BISMUTH; STRAIN; CAPACITORS